Recombinant expression of the larval excretory-secretory antigen TES-120 of Toxocara canis in the methylotrophic yeast Pichia pastoris - Fong, M.Y.; Lau, Y.L. (Springer Verlag (Germany), 2004)
A gene encoding the larval excretory-secretory antigen TES-120 of the dog ascarid worm Toxocara canis was cloned into the methylotrophic yeast Pichia pastoris. Specificity of the recombinant TES-120 antigen produced by the yeast was investigated. Forty-five human serum samples from patients infected with differentparasitic organisms, including 8 cases of toxocariasis, were tested against the recombinant antigen in immunoblot assays. Results from the assays showed that the recombinant TES-120 antigen reacted with sera from toxocariasis patients only. This highly specific recombinant TES-120 antigen can potentially be used for the development of an inexpensive serodiagnostic assay for human toxocariasis.